The concept of development of the neurosurgical service in Ukraine - Pedachenko, Eugene; Huk, Andriy (Ukrainian Neurosurgical Journal, 2014)
Introduction. Neurosurgical care, being highly specialized and highly-technological, is an indicator of state and society development. As of 01.01.2013 it was provided in 134 neurosurgical departments (in 2008 — in 131) on 3,910 beds (2008 — on 4,101) in regional centers and large cities of Ukraine. Changes over 50 years show a significant quantitative and qualitative improvement of neurosurgical service of Ukraine. Materials and methods. Based on analysis of statistics data and comparison of indicators of neurosurgical service with data of National Health Service England, EANO Committee on Ethics and other countries, neurosurgical service of Ukraine in 1998–2012 was evaluated, and a concept for its’ further development was proposed. Results. In Ukraine the «load» per neurosurgical bed remains low — only 12 operated patients, while more than 45.000 complex neurosurgical interventions performed annually, over the past 5 years total lethality decreased by 21%. Surgical activity increased from 42.1% — in 2008 to 44.1% — in 2012, the amount of neurosurgical operations of IV–V degree of complexity also increased (19,418 — in 2012, 17,392 — in 2008). Conclusions. For further improvement of quality and availability of neurosurgical service to the population of Ukraine, the concept for it’s development in 2014–2018 was proposed, that includes implementation of unified training program for neurosurgeons, recommended by the European Association of Neurosurgeons, high-tech neurosurgical care providing, and creating inter-regional neurosurgical centers, upgrading existing and creating new clinical protocols, guidelines and standards, orders of Ministry of Health of Ukraine that regulate delivery of neurosurgical care according to the healthcare reform plan, improving the material and technical resources of multihospitals which provide emergency neurosurgical care according to updated lists of equipment, neurosurgeons licensing and neurosurgical departments certification by the Ministry of Health of Ukraine in cooperation with the Ukrainian Association of Neurosurgeons, assessment of conditions and quality of neurosurgical care according to the updated clinical protocols.